2014
DOI: 10.1128/mcb.00492-12
|View full text |Cite
|
Sign up to set email alerts
|

GABP Transcription Factor (Nuclear Respiratory Factor 2) Is Required for Mitochondrial Biogenesis

Abstract: c Mitochondria are membrane-bound cytoplasmic organelles that serve as the major source of ATP production in eukaryotic cells. GABP (also known as nuclear respiratory factor 2) is a nuclear E26 transformation-specific transcription factor (ETS) that binds and activates mitochondrial genes that are required for electron transport and oxidative phosphorylation. We conditionally deleted Gabpa, the DNA-binding component of this transcription factor complex, from mouse embryonic fibroblasts (MEFs) to examine the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 39 publications
3
59
0
Order By: Relevance
“…For example, GABPA perturbation represses mitochondrial functions ( P < 10 −8 , Figure S6C, Table S6), consistent with its known role (Yang et al, 2014). YY1 perturbation is correctly (Goffart and Wiesner, 2003) predicted to represses oxidative phosphorylation (P<10 −10 ) and induce an innate immune response (P<10 −10 ), and is enriched for its ChIP-seq targets (Guo and Gifford, 2015)).…”
Section: Resultssupporting
confidence: 73%
“…For example, GABPA perturbation represses mitochondrial functions ( P < 10 −8 , Figure S6C, Table S6), consistent with its known role (Yang et al, 2014). YY1 perturbation is correctly (Goffart and Wiesner, 2003) predicted to represses oxidative phosphorylation (P<10 −10 ) and induce an innate immune response (P<10 −10 ), and is enriched for its ChIP-seq targets (Guo and Gifford, 2015)).…”
Section: Resultssupporting
confidence: 73%
“…Moreover, we observed a crucial role of mTORC1 in the regulation of mitochondrial function. First, of the 14 TFs attenuated in Rptor -deficient cells (Figure 5D), at least four TFs, including MYC (Li et al, 2005), YY1 (Cunningham et al, 2007), GABPA (Yang et al, 2014) and SREBF1 (Gilardi et al, 2014), have been implicated in mitochondrial functions. Second, focusing on mitochondrial proteins in the MitoCarta database (Calvo et al, 2016), we identified 129 mitochondrial proteins as Raptor-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies provided evidence that supports a role for NRF-2 in the whole process of mitochondrial biogenesis. Thus, mouse embryonic fibroblasts devoid of GAPBa exhibit reduced oxidative capacity and diminished ATP production associated with reduced mitochondrial mass [69]. Similarly to NRF-1, NRF-2/GABP also regulates the expression of genes involved in cell growth [70].…”
Section: Regulation Of Mitochondrial Biogenesis By Dna-binding Factorsmentioning
confidence: 98%